Model pembangunan komuniti - Sabran, Mohammad Shatar (Universiti Putra Malaysia Press, 2003)
Since independence in 1957, the government of Malaysia has implemented several projects and programs to help reduce the problem of poverty among the poor in the country. Billions of ringgit have been invested for that purpose. Though the problem of poverty has been reduced, the number of people who are poor remains high especially in the rural areas. One of the reasons for persistent poverty problems is the failure of rural development strategies and programs to alleviate poverty-related problem effectively. The Community Development Model proposed in this article focuses on five major elements believed to be effective in helping to alleviate the problems of poverty among the poor in rural areas. The five elements of the Community Development Model are local leaders, local residents, the core of community development, community development process and the results of community development. This model explains in detail the process that needs to be implemented by communities or agencies which are interested in helping the rural poor resolve the problems of poverty through the implementation of projects or programs. By following the processes suggested in the model, it will not only help resolve the poverty problems but also assist the country to invest in development projects that achieve the intended goals.